9.9k views
8 votes
37. Use the equation below to answer parts a-c.

3(-2x + 4) = -6x – 12
A. Solve the equation. Record your solution.
B. Does the equation have one solution, no solutions, or infinitely many solutions?
C. Explain how you know.
Copy
Cut
Paste

37. Use the equation below to answer parts a-c. 3(-2x + 4) = -6x – 12 A. Solve the-example-1
User Tim Maxey
by
5.0k points

2 Answers

5 votes

Answer:

Explanation:

Welp, we gotta solve for the solutions

Step 1

3(-2x + 4) = -6x – 12 Simplify

Step 2

3(-2x + 4) = -6x – 12 subtract 12 from the sides

-6x+12-12=-6x-12-12

-6x=-6x-24

Step 3

-6x=-6x-24 add 6x to the sides

-6x+6x=-6x-24+6x

0=-24 ??

Answer

No solution

User Mihal
by
5.9k points
4 votes

Answer:

Explanation:

Here you go mate

Use PEMDAS

Parenthesis

Exponent

Multiplication

Division

Addition

Subtraction

Step 1

3(-2x+4) =-6x-12 Equation/Question

Step 2

3(-2x+4) =-6x-12 Remove parenthesis

-6x+12=-6x-12

Step 3

-6x+12=-6x-12 Add 6x to sides

12=-12

Step 4

12=-12 Subtract 12 from sides

-24=0

Answer

No solutions

Hope this helps

User Labeeb Panampullan
by
4.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.